The Image of Women in Wilkie Collins’ Works - Djumayeva Gulnora Zokirovna (Genius Publishing Group, 2021)
The article provides an overview of Wilkie Collins’ work. At the same time, the artistic means in the works of Wilkie Collins have been extensively analyzed. The images in the works are also highlighted.
Keywords: Wilkie Collins; multidimensional characters; narrators; novels